Cost-effectiveness analysis of treatment regimens with obinutuzumab plus chemotherapy in Japan for untreated follicular lymphoma patients. (2nd October 2020) - Ohno, Shinya; Shoji, Ayako; Hatake, Kiyohiko; Oya, Naoko; Igarashi, Ataru
Abstract: Aims: Obinutuzumab (GA101; G) is a new treatment for follicular lymphoma (FL) that is anticipated to have greater efficacy than the current treatment, rituximab (R). The aim of this study was to evaluate the cost-effectiveness of G plus chemotherapy (G + Chemo) against that of R plus chemotherapy (R + Chemo) for patients in Japan with previously untreated FL. Materials and methods: We localized a previously reported cost-effectiveness model using the Japanese cost data. For estimating costs adapted in the model, FL patients treated with R were identified from Japanese hospital-based claims database and classified into three treatment regimen groups according to chemotherapies used with R: CHOP, CVP, and bendamustine (B). Based on services per patient and cost items, parameters determining the cost amounts were derived using a multivariate generalized linear mixed model to estimate the direct medical costs for each treatment regimen group for G and R. For the utility, same values in the previous model were used. Lifetime cost and quality-adjusted life year (QALY) were estimated under the payer's perspective. Results: The calculated incremental cost-effectiveness ratios (ICERs) in million JPY per QALY for G-CHOP vs. R-CHOP, G-CVP vs. R-CVP, and G-B vs. R-B were 5.4, 4.3, and 4.8, respectively. ICERs were lower than 7.5 million JPY per QALY, which is the cost-effectiveness threshold for cancer treatments, and showed that G + Chemo is a cost-effective treatment regimen for Japanese patients with previously untreated FL. Lifetime direct medical costs were lowest in the R-B group because hospitalization costs that accounted for most of the total cost were lowest in this group. Limitations and conclusions: The cost-effectiveness of G + Chemo is acceptable in Japan. Differences in the direct medical costs among treatment regimen groups were mostly due to hospitalization costs. This is probably because many Japanese hematologists choose inpatient treatments over outpatient treatments in CHOP-based induction therapy.